1984
DOI: 10.1113/jphysiol.1984.sp015161
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the oxygen deficit‐oxygen debt relationships with beta‐adrenergic receptor blockade in man.

Abstract: SUMMARY1. The effects of fi-adrenergic receptor blockade (100 mg oral metoprolol) or matched placebo on gas exchange kinetics were studied in six males. Ventilation and gas exchange were monitored in four transitions for each treatment from loadless pedalling (0 W) to a selected work rate (100 W) and back to 0 W. Breath-by-breath data were averaged for analysis.2. Oxygen uptake (Po.) kinetics were significantly slowed at the onset of exercise and recovery by fl-blockade. This resulted in larger oxygen deficit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 43 publications
(75 reference statements)
3
28
1
Order By: Relevance
“…Beta-adrenergic receptor blockade slowed VO 2 kinetics in MOD by reducing heart rate and subsequently O 2 transport (Hughson, 1984). Several research groups have also slowed VO 2 kinetics with hypoxia (lower fraction of inspired O 2 (FiO 2 ) and thus reducing arterial partial pressure of oxygen (PaO 2 )) across varying work rates (DeLorey et al, 2004c;Hughson & Kowalchuk, 1995;Springer et al, 1991).…”
Section: ) Oxygen Deliverymentioning
confidence: 99%
“…Beta-adrenergic receptor blockade slowed VO 2 kinetics in MOD by reducing heart rate and subsequently O 2 transport (Hughson, 1984). Several research groups have also slowed VO 2 kinetics with hypoxia (lower fraction of inspired O 2 (FiO 2 ) and thus reducing arterial partial pressure of oxygen (PaO 2 )) across varying work rates (DeLorey et al, 2004c;Hughson & Kowalchuk, 1995;Springer et al, 1991).…”
Section: ) Oxygen Deliverymentioning
confidence: 99%
“…The authors suggested that the slower heart rate kinetics during work-to-work transition may be due to a reduced influence of parasympathetic neural activity on the control of heart rate at the onset of exercise. Furthermore, Hughson and his colleagues [48,49] found that V . O 2 kinetics during exercise were slowed by administration of β-blockers in healthy participants.…”
Section: O 2 Deliverymentioning
confidence: 99%
“…The discussed findings indicate that the rate of oxygen uptake at the onset of exercise may be affected by the interventions contributing to oxygen delivery to the working muscles (especially at high-power output exercise) [37,38,40] and the factors affecting the rate of muscle metabolism [41][42][43][44]16].…”
mentioning
confidence: 99%
“…An administration of β-adrenergic blockade slows down the O 2 on-kinetics in humans [41], whereas an administration of L-NAME, causing an inhibition of nitric oxide synthase, significantly accelerates the O 2 on-kinetics in a thoroughbred horse [42], as well as in humans [43,44]. The authors concluded that the intrinsic inertia of oxidative metabolism at the onset of heavy-intensity exercise may result from an inhibition of mitochondrial respiration by nitric oxide.…”
mentioning
confidence: 99%